Formulating Character Development Policy in Vocational Higher Education: A Qualitative Study and the V-CODE Model - Andrianto, Tomy; Susanto, Eko; Syukri, Muhammad Yazidus; Sulistiana, Oktavera; Irawan, Candra (Journal Integration of Social Studies and Business Development, 2025)
This study investigates the formulation and implementation of character development policies in vocational higher education institutions in Indonesia. Using a qualitative design, data were collected through panel surveys involving key stakeholders at multiple institutional levels, including lecturers, department heads, and vice directors. The study explores stakeholders' perceptions regarding the urgency of character education, the values to be instilled, implementation strategies, challenges, and evaluation mechanisms. Findings reveal a strong consensus on the importance of integrating character development into the core curriculum, yet also highlight critical challenges such as fragmented policy implementation, limited faculty capacity, and inadequate evaluation systems. National regulations are recognized as valuable frameworks, but their operationalization at the institutional level remains inconsistent. To address these gaps, the study introduces the V-CODE Model (Vocational Character-Oriented Development & Evaluation), a conceptual framework comprising five interconnected components: driving factors, stakeholder involvement, policy formulation, implementation strategies, and evaluation mechanisms. The model emphasizes participatory policy design, curriculum-wide integration, and feedback loops reinforcing continuous improvement. This research contributes to theory and practice by offering a contextually grounded model to guide vocational institutions in building sustainable and impactful character education systems. The study also provides policy recommendations for aligning institutional practices with national education goals and labor market expectations.